Legal Responsibility for Land Deed Officials (PPAT) for Forgery of Land Sale and Purchase Deeds as The Basis for Transfer of Land Rights (Study of Decision Number 773/Pid.B/2021/Pn Smg) - Dwi Saputra, Andy Bharata Yudha; Hafidz, Jawade (Jurnal Konstatering, 2025)
The preparation of a land sale and purchase deed by a Land Deed Making Officer (PPAT) is part of the legal procedure in the process of transferring land rights, which forms the basis for the legality of the transaction. However, in practice, there are cases where PPATs are involved in falsifying land sale and purchase deeds, which can be detrimental to the parties involved. This study aims to analyze the legal responsibility of PPATs regarding falsification of land sale and purchase deeds as the basis for transferring land rights, with a focus on the case study of Decision Number 773/Pid.B/2021/PN Smg. The type of research used is normative juridical, with a case-based and statutory approach, which examines the application of law in cases of land deed forgery. This research identifies legal violations committed by Land Deed Officials (PPAT) in falsifying land sale and purchase deeds and their impact on the transfer of land rights. Based on the analysis, it can be concluded that the actions of Land Deed Officials (PPAT) who falsify authentic deeds can be held accountable under civil, criminal, and administrative law. PPATs can be sued for compensation, subject to criminal sanctions under the Criminal Code, and administrative sanctions such as warnings or dismissal. A forged deed can give rise to disputes that can be brought to court, with claims for compensation under Article 1320 of the Civil Code, as in the case of Semarang District Court Decision Number 773/Pid.B/2021/PN.Smg which annulled a land sale and purchase deed due to signature forgery.